Development of a Fast Track of Care for Stroke Patients: an Application of a Case Management Model - Promtee, Phraiwan (Journal of Health Science of Thailand, 2017)
The objective of this study was to develop a fast track of care for stroke patients receiving treatment with recombinant tissue plasminogen activator (rt-PA) by using a case management model. Participants consisted of two groups: (1) 30 stroke patients receiving rt-PA and 5 caregivers, and (2) 10 hospital staff including doctors, nurses, pharmacists, nutritionists, and physical therapists. The study was conducted from October 2010 to September 2011. The study process comprised of situational analysis, operation, and evaluation. The instruments were divided into three categories: (1) research operation tools which included the Barthel Activities of Daily Living (ADL) Index, a care plan, and a standard nursing care; (2) quantitative data collection tools: a data record form for stroke patients receiving rt-PA, an evaluation form for patient’s satisfactions, an evaluation form for nursing practice following a care plan for stroke patients, and an evaluation form for nursing practice following a standard nursing care for stroke patients; and (3) qualitative data collection tools: a questionnaire for interviewing stroke patients and caregivers, and a questionnaire for hospital staff discussion. Data were collected from medical records, interviews, and focused-group discussions. Frequency and percentage distributions were used to analyze quantitative data, and content analysis was used to analyze and summarize qualitative data. It was found that the case management model was useful to reduce waiting time for stroke patients to receive rt-PA from 102 minutes to 66 minutes, and 16 patients (53%) received rt-PA within 60 minutes. The length of hospital stay reduced from 7 to 4 days. Cerebral hemorrhage due to the treatment of rt-PA decreased from 16% to 6%; and the risk of disability decreased from 67% to 93%. The patient’s satisfaction increased from 80% to 97%. Moreover, the incidence of aspirated pneumonia decreased from 16% to 0%, and the incidence of pressure ulcer decreased from 8% to 0%. Also, there was no falls occurring during this study. In conclusion, the case management model helped to develop continuing care for stroke patients receiving rt-PA and cooperation among hospital staff. As a result, care for these patients and communication among hospital staff were more effective.